Simulación numérica del flujo en una chimenea con recuperación de calor - Guijosa Montalvo, José Juan (My University, 2013)
Simulación numérica del flujo en una chimenea con recuperación de calor
Simulación numérica del flujo en una chimenea con recuperación de calor
Keywords: Simulación numérica del flujo en una chimenea con recuperación de calor